Tra estetica della totalità e immaginazione melodrammatica. Castellucci e Wagner - Ceraolo, Francesco (Scenari, 2021)
The essay analyses Romeo Castellucci’s Wagnerian staging (Parsifal and Tannhäuser) focusing in particular on what the crossings between aesthetics of totality and forms of the melodramatic imagination have produced, and can produce, in terms of aesthetic and theoretical results in contemporary theatre. The experience of Romeo Castellucci is also read within a wider philosophical and theatrical reconsideration of the work of Richard Wagner since the 2000s. On the one hand, in fact, Wagner has been re-evaluated as the theoretician of a political and artistic praxis that is opposed both to critical negative thinking and to the relativistic derivatives of postmodernism (Badiou, Žižek); on the other, Wagner’s theatrical ideal has come to represent the crucial reference for the overcoming of pure performativity in the name of a theatrical experience intended as the encounter between the symbolic order of the text and the impure real of the representation, i.e. between the eternity of the idea and the instant of the staging.